Aumento da probabilidade diagnóstica de Síndrome de Cushing subclínica em amostra de população de pacientes obesos com diabetes mellitus do tipo 2 - Caetano, Maria Silvia Santarem [UNIFESP] (2008)
Endogenous Cushing’s syndrome (CS) is unusual. Patients with subclinical CS (SCS) present altered cortisol dynamics without obvious manifestations. CS occurs in 2-3% of obese poorly controlled diabetics. We studied 103 overweight adult outpatients with type 2 diabetes to examine for cortisol abnormalities and SCS. All collected salivary cortisol at 23:00h and salivary and serum cortisol after a 1mg dexamethasone suppression test (DST). Patients whose results were in the upper quintile for each test (253ng/dL, 47ng/dL and 1.8ìg/dL, respectively for the 23:00h and post-DST saliva and serum cortisol) were re-investigated. Average values from the upper quintile group were 2.5- fold higher than in the remaining patients. After a confirmatory 2mgx2day DST the investigation for CS was ended for 61 patients with all normal tests and 33 with only one (false) positive test. All 8 patients who had two abnormal tests had subsequent normal 24h-urinary cortisol, and 3 of them were likely to have SCS (abnormal cortisol tests and positive imaging). However, a final diagnosis could not to be confirmed by surgery or pathology. Although not confirmatory, the results of this study suggest that the prevalence of SCS is considerably higher in populations at risk than in the general population.